Reducing properties of 1, 2-dipyridyl-1, 2-disodioethanes: chemical validation of theoretical and electrochemical predictions. Issue 52 (13th May 2016) - Azzena, U.; Carraro, M.; Pisano, L.; Mocci, F.; Antonello, S.; Maran, F.
Abstract : Theoretical calculations and electrochemical analysis were used to set up a relative scale for the reducing strength of the dianions of 1, 2-dipyridylethenes, validated by studying their reactivity towards halogenated benzoic and arylacetic acids. Abstract : The reducing properties of highly delocalized radical anions and dianions of 1, 2-di(hetero)arylethenes were investigated by theoretical calculations at the PBE0/6-311+G(d, p)/IEFPCM level. The results correlated nicely with the reduction potentials determined by analysis of the voltammetric curves for the reduction of the parent alkenes, and this allowed a reliable scale for their relative reducing strength to be established. In full agreement with calculations and electrochemical results, use of the appropriate 1, 2-dipyridyl-1, 2-disodioethane as a base led to the successful α-alkylation of bromophenylacetic acids under mild reaction conditions, thus avoiding the competitive reductive cleavage of aromatic C–Br bonds.